Developing an ultrasensitive immunochromatographic assay for authentication of an emergent fraud aminopyrine in herbal tea. (16th April 2023) - Fang, Yalin; Wang, Zian; Quan, Qiqi; Li, Zhaodong; Pan, Kangliang; Lei, Yi; Yao, Xiaojun; Li, Xiangmei; Shen, Xing; Koidis, Anastasios; Lei, Hongtao
Highlights: Rational hapten design strategy for aminopyrine was provided. A specific antibody with IC50 of 3.00 ng/mL was obtained for the first time. Immunochromatographic assay for aminopyrine in herbal tea was proposed. Abstract: Aminopyrine is a nonsteroidal anti-inflammatory drug only for medical purposes, however, it has been illegally added in traditional Chinese herbal teas for fraud activity recently. In this study, a specific antibody against aminopyrine with IC50 of 3.00 ng/mL was obtained for the first time by a rational hapten design. Furthermore, an ultrasensitive gold nanoparticles immunochromatographic assay (AuNPs-ICA) for determination of aminopyrine based on a portable reader was firstly developed, with cut-off value of 100.00 ng/mL, limit of detection (LOD) of 4.80 ng/mL and limit of quantification (LOQ) of 5.71 ng/mL for herbal tea, respectively. The recovery rates ranged from 93.21 % to 105.61 %, with inter-assay coefficient of variation (CV) from 1.08 % to 3.82 %. Additionally, 24 blind samples were examined simultaneously by AuNPs-ICA and LC-MS/MS, demonstrating a good consistency for each other. The proposed AuNPs-ICA is an ultrasensitive and reliable tool for on-site surveillance screening of fraud additives in herbal tea.